2021
DOI: 10.3389/fvets.2021.712226
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial and Temporal Characterization of Gut Microbiota in Broilers

Abstract: The gut microbiota of chickens plays an important role in host physiology. However, the colonization and prevalence of gut microbiota have not been well-characterized. Here, we performed 16S rRNA gene sequencing on the duodenal, cecal and fecal microbiota of broilers at 1, 7, 21, and 35 days of age and characterized the dynamic succession of microbiota across the intestinal tract. Our results showed that Firmicutes was the most abundant phylum detected in each gut site at various ages, while the microbial dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 71 publications
3
25
0
Order By: Relevance
“…Gut microbiota plays a crucial role in the physiology of chickens and disturbances in the composition of the gut microbiome may cause serious disorders ( Zhou et al., 2021 ), not only withing the gastrointestinal tract but also in other organs, including the central nervous system ( Cao et al., 2021 ). In fact, although previous works on the use of phage therapy in chickens focused solely on testing the presence of certain pathogenic bacteria and/or specific symptoms in birds, recent studies indicated the importance of investigating microbiomes during and after specific treatment procedures ( Clavijo et al., 2022 ; Lorenzo-Rebenaque et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota plays a crucial role in the physiology of chickens and disturbances in the composition of the gut microbiome may cause serious disorders ( Zhou et al., 2021 ), not only withing the gastrointestinal tract but also in other organs, including the central nervous system ( Cao et al., 2021 ). In fact, although previous works on the use of phage therapy in chickens focused solely on testing the presence of certain pathogenic bacteria and/or specific symptoms in birds, recent studies indicated the importance of investigating microbiomes during and after specific treatment procedures ( Clavijo et al., 2022 ; Lorenzo-Rebenaque et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, Wen et al found a relatively high abundance level of Romboutsia and significantly higher egg-laying efficiency in chickens ( Wen et al, 2021 ). Butyricicoccus , a potential active ingredient in probiotic formulations and a producer of short chain fatty acids, was associated with better growth and development in broilers when its relative abundance in the cecum was high ( Zhou et al, 2021 ). And Lactobacillus genus was able to increase the expression level of immune cytokines in the intestinal tract, which contributed to clearing the oocysts in the intestine, consistent with the statistical results of fecal oocysts.…”
Section: Discussionmentioning
confidence: 99%
“…Eggs are formed in the maternal reproductive tract, and the embryo in the egg grows and develops into a chick after 21 days of incubation. Previous research confirmed the presence of microorganisms in the maternal reproductive tract and digestive tracts of 1-day-old chicks (Pajurek et al, 2019;Zhou et al, 2021). Several studies have shown that hen gut and fecal microbes are associated with both egg formation and fertility (Elokil et al, 2020a,b).…”
Section: Introductionmentioning
confidence: 75%
“…Our study demonstrated that egg yolk and white are not free from microorganisms, in agreement with our earlier claim that eggs are not formed in a sterile environment ( Wen et al, 2021 ). Similarly, we previously characterized the gut microbiota of 1-day-old chicks ( Zhou et al, 2021 ). Therefore, one of the aims of this study was to fill the gap between studies on the microbiota in hens and chicks.…”
Section: Discussionmentioning
confidence: 99%